Implementation of the Principle of "Ma Lā Yatimmu Al-Wājib Illā Bihi Fahuwa Wājib" in Corporate Social Responsibility (CSR) Obligations - Muhammad Agus Nursyamsi (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
This research discusses the implementation of the fiqh rule "Ma Lā Yatimmu al-Wājibu Illā Bihi Fa huwa Wājib" in Corporate Social Responsibility (CSR) obligations. Even though CSR has become an important part of business strategy, there are still many companies that do not apply social principles in balance with economic goals. A mismatch between social values ​​and company profitability often hinders the positive impact of CSR. The aim of this research is to examine the application of fiqh rules in CSR and the challenges faced by companies. This research uses a qualitative approach with document analysis and interviews with CSR practitioners and fiqh experts. The research results show that the implementation of CSR based on fiqh principles is still hampered by limited understanding of fiqh among entrepreneurs. Despite increasing awareness, many companies have not fully integrated Islamic values ​​in their CSR policies. More supportive government and regulations are important factors in strengthening corporate social awareness. Apart from that, strategic recommendations for increasing company compliance with fiqh-based CSR need to be considered, especially in the aspects of education and training.